2021
DOI: 10.4103/jehp.jehp_600_20
|View full text |Cite
|
Sign up to set email alerts
|

Relation between stress, time management, and academic achievement in preclinical medical education: A systematic review and meta-analysis

Abstract: Identifying the learners' problems is important. Besides, many factors are associated with academic failure, among which time management and stress are more important than any others based on evidence. By using a systematic review and meta-analysis, this study aims to synthesize the findings of studies about the correlation of time management and stress with academic failure to suggest a more in-depth insight into the effect of these two factors on academic failure. Four databases were searched from the incept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Medical education can be a stressful experience for students[ 1 2 3 ] and may have a devastating effect on their psychological well-being. [ 1 4 ] Hence, it is believed that medical students are more likely than other people to be exposed to mental disorders,[ 5 ] so one of the concerns in the public health domain across the globe is the mental and psychological welfare of medical students, which is associated with the quality of health care provided by them.…”
Section: Introductionmentioning
confidence: 99%
“…Medical education can be a stressful experience for students[ 1 2 3 ] and may have a devastating effect on their psychological well-being. [ 1 4 ] Hence, it is believed that medical students are more likely than other people to be exposed to mental disorders,[ 5 ] so one of the concerns in the public health domain across the globe is the mental and psychological welfare of medical students, which is associated with the quality of health care provided by them.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, assessment preparation plays an important role in meeting the challenge of assessment. Studies have shown that helping students control their negative thoughts and advising them on learning skills and time management will maximise their learning [ 102 , 103 ]. In our framework, we believe that teachers play the central role in maximising learners’ behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Stress has severe consequences on those within the medical field, increasing rates of depression, dropout, alcohol abuse, illicit drug use, and suicide, and can even impair patient care 20,21 . Although medical students have significantly higher rates of stress than the general population, 20–22 organization and time management, which the guides were shown to provide, can be effective positive coping mechanisms and can prevent burnout 22–24 . In turn, these soft skills may improve academic achievement 24 .…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Although medical students have significantly higher rates of stress than the general population, [20][21][22] organization and time management, which the guides were shown to provide, can be effective positive coping mechanisms and can prevent burnout. [22][23][24] In turn, these soft skills may improve academic achievement. 24 Although use of the guides did not correlate with improved examination scores in this small sample, the notable effects on stress relief, organization, time management, and self-confidence in meeting academic expectations may play a much larger role in the holistic wellness and success of medical trainees in their first year and beyond.…”
Section: Discussionmentioning
confidence: 99%